THE EFFECT OF TEACHING ORAL COMMUNICATION STRATEGIES ON INDONESIAN EFL LEARNERS’ SPEAKING SKILL - Yuniarti Yuniarti (University of Kuningan, 2017)
This study reports on applying the teaching of oral communication strategies (OCSs) in the speaking class to improve students’ speaking skill. It was designed in a quasi-experimental research. 53 undergraduate EFL students in the English Department of a private university in Kuningan were purposively chosen as the participant of the course. They were grouped into control and experimental class. The course material of OCSs was adapted from a study conducted by Nakatani (2005). The effects of teaching OCSs were assessed by two types of data collection: the participants’ pre-test and posttest speaking scores, and the transcription from the tests. The first result showed that the most frequently used OCSs in the speaking class were filled pauses, interlanguage-based, false starts, providing active response, first-language-based, and approximation strategy. Then, second, the t result indicated that tobs was greater than tcrit. Therefore, it can be concluded that the teaching of OCSs in the EFL speaking class had a significant effect in developing students’ speaking skill. It indicates that such training activities are relatively applicable to use in the language classroom.Keywords: EFL teaching, oral communication strategies, speaking skill